Предмет: Математика, автор: q100n228

Упростить выражение:
1) 7 (2b — 4с) + 5c
2) — 10а — 5(-а + 8) — 14
3) - 2 (13х + 5y) — 16х
4) (12а + 5d) — 4 (18а — d)
5) - (17x - 2y) – 2 (7y + 3x)
6) - 5 (За + 2b) — (4а + 7b) 6
7) 16 (5c + b) — (30c — 8b)
8) 12а — (7 – 2а) + (15а – 12)
9) 0,9 (4y - 2) - 0,5 (30y – 4)
10) – 22а – 2 (- 2а + 7) + 14​

Ответы

Автор ответа: ilpil0
1

Пошаговое объяснение:

1) 14b-28c+5c= 14b-23c

2) -10a+5a-40-14= -5a-26

3)-26x-10y-16x=-42-10y

4) 12a+5d-72a+4d=-50a+9d

5)-17x+2y-14y-6x=--23x-12y

Мне лень остальные делать :)


q100n228: мог просто ответы написать
Похожие вопросы